Systematization of results of the Socio-educational Accompaniment Project for Children's Caregivers to Prevent Violence-2019 - Castillejo Olán, Rubén; Márquez Allauca, Victoria María; Morán Quinteros, Katherine; Merchán Gavilánez, María Luisa (Revista Minerva, 2023)
The project Socio-educational accompaniment to regular caregivers of children for the prevention of violence FCI-045-2019, of the Faculties of Philosophy, Letters and Educational Sciences and Pilot of Dentistry of the University of Guayaquil, aimed to contrast the results published by its researchers. A contrasting methodology was used by means of the analytical-synthetic method and the argumentation methodology of Toulmin et al. (1979), between publications of the last five years, by relevance, and the results published by the researchers. The study categories were: bonding parenting competencies and family socioeconomic level, parenting styles, child identity and autonomy, parenting styles in the face of child violence, violence during COVID-19 and parenting competencies-promotion of parenting styles. The results show that there is a relationship of coincidence between the theoretical conceptions systematized in the scientific literature, the publications of the researchers of the project, on the categories-variables studied, with the social consequences manifested in the Ecuadorian context and particularly, in the community-educational context of Guayaquil, which corroborate undesired states of the variables parenting styles, child violence and identity and autonomy. It is agreed to propose ways of systematic improvement to the subjects responsible for the upbringing of children.
Keywords: family education; child abuse; child rearing; social status